2017
DOI: 10.1177/1359105317713359
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating and binge drinking among adolescents: The role of drinking and eating motives

Abstract: This study aimed to investigate the motivations underlying binge eating and binge drinking in a sample of 302 adolescents. Our findings showed that binge eating was significantly correlated with gender, environmental, emotional, and social eating. Hierarchical multiple regression analysis indicated that emotional and environmental eating were significant positive predictors of binge eating, whereas binge drinking was significantly correlated with enhancement, social, and coping motives. Only enhancement motive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…The analysis showed that after controlling for the mediating effect of PNEES-N, PNEES-P continued to significantly predict binge eating. The tendency to overeat in response to positive emotions could be integrated into current models of eating disorders, especially when addressing relapse prevention (Pompili and Laghi 2017;Sultson et al 2017). In the present experiments, out of 18 animals, only 12 were used in which direct stimulation of the hypothalamus did not cause a food reaction, but only an exploratory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis showed that after controlling for the mediating effect of PNEES-N, PNEES-P continued to significantly predict binge eating. The tendency to overeat in response to positive emotions could be integrated into current models of eating disorders, especially when addressing relapse prevention (Pompili and Laghi 2017;Sultson et al 2017). In the present experiments, out of 18 animals, only 12 were used in which direct stimulation of the hypothalamus did not cause a food reaction, but only an exploratory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…As currently known, BED refers to non-chemical dependence and, apparently, is formed like other types of addictive behavior (Iemolo et al 2012;Pompili and Laghi 2017). It was shown that an activating effect of post-training lateral hypothalamic self-stimulation on aversive and appetitive classical conditioning (Ettenberg and White 1978), as well as post-training ICSS could also be an effective treatment for improving implicit visual discrimination learning and memory (Garcia-Brito et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In considering why adolescents repeatedly engage in binge behaviors, it has been argued that they serve a similar function and purpose such as regulating emotions and/or escaping from negative emotions and coping with distress. [17][18][19][20][21] Above all, women who binge eat and drink often report the two behaviors in response to feeling lonely, bored or powerless in relation to their partners or they describe bingeing as a means of escape from fear of failure or feelings of low self-esteem and inadequacy. [22][23][24] Indeed, recent studies showed that binge eating and binge drinking among young people were associated with difficulties in emotion regulation (ER) and in dealing with situations involving negative emotions.…”
mentioning
confidence: 99%
“…28,29 Although there is a growing interest in analyzing emotional factors underlying the engagement in binge behaviors, only few studies have examined the role of ER in binge eating and binge drinking among adolescents. For instance, the important role of coping (or emotional) motives has been highlighted as the main triggering factor of binge eating among adolescents 20 ; particularly, it has been noted that binge eaters tended to use such behavior to avoid or reduce perceived negative affective states. On the other hand, binge drinking was predicted by enhancement motives, such that adolescents, rather than managing aversive states, engaged in binge drinking to have fun, to seek excitement, to make a party more enjoyable, and to get high and drunk.…”
mentioning
confidence: 99%